My Math GPS Elementary Algebra Guided Problem Solving - Cornick, Jonathan; Guy, Michael; Puri, Karan (Open textbook library., 2016)
My Math GPS: Elementary Algebra Guided Problem Solving is a textbook that aligns to the CUNY Elementary Algebra Learning Objectives that are tested on the CUNY Elementary Algebra Final Exam (CEAFE). This book contextualizes arithmetic skills into Elementary Algebra content using a problem-solving pedagogy. Classroom assessments and online homework are available from the authors.